Răspuns:
2+5-7+2-6+9=7-7+2-6+9= -4+9 = 5
(+3-12+7)x(-8+6+5)=-2 x 3 = -6
-5 x[+2 x(-9-3+5)+15]+17= -5 x [2 (-9-3+5)]+17= -5 x 16 +17 = -80 + 17= -63
2 x{+7-5 x[-3 x (+2-5+6-4) x (-4+5-3)+8]} = 2 x {7-5[-3 x(-1) x (-2) +8]}=2 x [ 7-5 ( (-6)+8)] =2 x (2 x 2) =2 x 4= 8
+550:[-5x(+146-375+135):(+281-374+124)-124] = 550 : [-5x(-94) :31-124] = 550:[-5x (-3,03) - 124]=550:(15,15 -124 )=550:(-108,85) = -5,05 (Nu stiu daca am gresit eu sau daca tu ai copiat gresit ex )
[tex](-2)^{3} - (-3)^{2} -(-1)^{4} -(- 1)^{5}[/tex] = (-8) +9+1-1 = (-8) +9 = 1
[tex](-3)^{80} : (-3)^{78} - (-7)^{25} : 7^{23} +[(-5)^{8}]^{3} : [(5)^{11} ]^{2} = (-3)^{80-78} -(-7) ^[25-23]^{2}+(-5)^[24-22]^{2} = (-3)^{2} + 7^{2} - 5^{2} = 9+49+25 =83[/tex]
Bafta!